Automated aerodynamic optimization of the position and posture of a bobsleigh crew - Winkler, A.; Pernpeintner, A. (Procedia Engineering, 2010)
CFD-simulations were conducted to simulate the flowfield around a bobsleigh. A simplified crew model of the pilot and the brakeman of a 2-man bobsleigh was generated. The model was used to perform the fully automated optimization of the crew posture and position. Furthermore, a genetic optimization algorithm from the software package DAKOTA was used in order to search for the optimum crew position and posture. The considerable effect of the crew position and posture on the aerodynamic drag was verified and an optimum crew posture and position was found that deviates from a maximum ducking posture of the brakeman.